Multifunctional Macrocyclic Receptors as Templates for Aromatic Amino Acids: A Rare Example of a Highly Selective Multi‐Input Multi‐Output Chemo‐"Logic Gate". Issue 9 (6th May 2013) - Fraschetti, Caterina; Filippi, Antonello; Crestoni, Maria Elisa; Ema, Tadashi; Speranza, Maurizio
Abstract Proton‐bound [M⋅H⋅G]+ diastereomeric complexes between some chiral aromatic amino acids or dipeptides (G) and a chiral multifunctional macrocyclic receptor (M=Chirabite‐A) undergo, in the gas phase, highly selective substitution and addition reactions by amines, such as 2‐aminobutane and piperidine. All the [M⋅H⋅G]+ complexes follow time‐dependent monoexponential decays. In some cases, the kinetic curves exhibit a plateau revealing the presence of unreactive [M⋅H⋅G]+ structures. In them, the amino acid is accommodated in the macrocycle cavity in the zwitterionic form by sharing its acidic hydrogen atoms with the pyridine nitrogen atoms of the host. The same interactions are structurally inaccessible to G=dipeptides or monofunctional amines, which then can be readily released from [M⋅H⋅G]+. When the amino acid interacts with the amidocarbonyl oxygen atoms pointing outside the macrocycle cavity, it saves the canonical structure and can be readily displaced by the amine. The Chirabite‐A may act as an efficient template for aromatic amino acids by releasing them or not depending upon the amino acid configuration and the basicity of the amine. These unique properties confer to the gas‐phase diastereomeric [M⋅H⋅G]+ complexes the features of multi‐input multi‐output chemo‐"logic gates".